2011
DOI: 10.1103/physreva.84.043607
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative hydrodynamic equation of a ferromagnetic Bose-Einstein condensate: Analogy to magnetization dynamics in conducting ferromagnets

Abstract: The hydrodynamic equation of a spinor Bose-Einstein condensate (BEC) gives a simple description of spin dynamics in the condensate. We introduce the hydrodynamic equation of a ferromagnetic BEC with dissipation originating from the energy dissipation of the condensate. The dissipative hydrodynamic equation has the same form as an extended Landau-Lifshitz-Gilbert (LLG) equation, which describes the magnetization dynamics of conducting ferromagnets in which localized magnetization interacts with spin-polarized c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Both adiabatic and sudden preparation was carefully considered, and it was demonstrated that this state is stable for sufficiently small spiral wave vectors. However, despite the recent observation of a (quasi)condensate of magnons [25,26], few studies have been devoted to spin superfluidity in ultracold spinor gas [27][28][29][30], even though this phenomenon has played a prominent role in liquid helium systems [31]. Furthermore, the interplay of mass and spin superfluidity has not been addressed in the ultracold-atom context to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Both adiabatic and sudden preparation was carefully considered, and it was demonstrated that this state is stable for sufficiently small spiral wave vectors. However, despite the recent observation of a (quasi)condensate of magnons [25,26], few studies have been devoted to spin superfluidity in ultracold spinor gas [27][28][29][30], even though this phenomenon has played a prominent role in liquid helium systems [31]. Furthermore, the interplay of mass and spin superfluidity has not been addressed in the ultracold-atom context to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed derivation is given in Refs. [12,16], and the resulting equations of motion are written as…”
Section: Modelmentioning
confidence: 99%
“…(13c) does not diverge at Γ = 0 since ∇ · (n tot v mass ) ∝ Γ: Eq. (13c) is also written as [16] M ∂ ∂t…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations